Is it wrong to try to pick up girls in a dungeon? on the side : sword oratoria. 2 - Omori, Fujino (Yen Press, 2018)
The peerless Sword Princess can't seem to forget the sight of a young boy running away from her. Watching his receding back brings up memories from her own past and she begins to question her sole ideal of devoting everything to become stronger. For the first time ever, is Aiz is a bit troubled by her heart like any normal young girl?